Impacts of the pandemic: the role of ‘face masks’ in hospitality and tourism service provision - Christou, Prokopis A.; Savva, Rodoula (My University, 2021)
This study postulates that ‘masks’ on the face of service employees during the pandemic had a deeper role to play other than shielding their own and tourists’ health. A mixed methodological approach revealed various personal, physical and psycho-social impacts of face masks in services. Contrary to other domains such as the theatre, entertainment and events industry, face masks possess a negative valence since they deprive expressions of emotions and possibilities of channelling to guests positive states. Even so, this study has proven that service providers can be extremely adoptive, resilient and very good transferors of hospitality even if masks hide probably the most welcoming aspect of the hospitality notion and powerful tool, their ‘smiles’. A hermeneutical understanding of face masks in contemporary society is provided for theoretical and practical consideration. Highlights Face masks in tourism service provision may carry a negative valence. Tourism service providers ‘smile’ through their eyes when wearing masks. Guests receive hospitality even if employees think that masks deprive its offering.
Keywords: Face masks; Impacts; Pandemic; Dervices; Tourism; Tourist experience